2010
DOI: 10.1002/hep.23483
|View full text |Cite
|
Sign up to set email alerts
|

The histogenesis of regenerative nodules in human liver cirrhosis

Abstract: Here, we investigate the clonality and cells of origin of regenerative nodules in human liver cirrhosis using mitochondrial DNA (mtDNA) mutations as markers of clonal expansion. Mutated cells are identified phenotypically by deficiency in the entirely mtDNA encoded cytochrome c oxidase (CCO) enzyme by histochemical and immunohistochemical methods. Nodules were classified as either CCO-deficient or CCO-positive, and among 526 nodules from 10 cases, 18% were homogeneously CCO-deficient, whereas only 3% had a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 24 publications
1
68
0
Order By: Relevance
“…It raises a possibility that human HCC may originate from enriched progenitor cells in the liver under conditions in which the proliferation of hepatocytes is inhibited. By tracing the mitochondrial DNA mutations, Lin et al recently showed that some monoclonal human cirrhotic regenerative nodules could be derived from hepatic progenitor cells (25). However, the details still need to be studied by using appropriate animal models.…”
Section: Discussionmentioning
confidence: 99%
“…It raises a possibility that human HCC may originate from enriched progenitor cells in the liver under conditions in which the proliferation of hepatocytes is inhibited. By tracing the mitochondrial DNA mutations, Lin et al recently showed that some monoclonal human cirrhotic regenerative nodules could be derived from hepatic progenitor cells (25). However, the details still need to be studied by using appropriate animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology: Biliary fibrosis is the subtype of hepatic fibrosis which is frequently associated with ductular reactions (hyperplasia/proliferation which form pseudo-bile ducts) and structural alteration [24,40]. The biliary fibrotic lesions of the present cattle were characterized by pseudolobule formation, proliferation/hyperplasia of bile ducts and fibrotic bridges.…”
Section: Discussionmentioning
confidence: 99%
“…The regenerating nodules can be either polyclonal or monoclonal in origin [48]. The monoclonal origin of RN cells was reported by Lin et al [49], who stated that the cells of origin are more likely to be a facultative stem cell from the biliary tree.…”
Section: Inflammatory Bed Inflammasomes and Regenerating Nodules Durmentioning
confidence: 99%